2017
DOI: 10.1039/c7nr00261k
|View full text |Cite
|
Sign up to set email alerts
|

A one-dimensional random laser based on artificial high-index contrast scatterers

Abstract: The realization of a one-dimensional (1D) random laser (RL) by using artificially fabricated scatterers is reported in this letter, and the lasing characteristic has also been investigated comprehensively. The manipulation of the lasing mode in the 1D microwire (MW) RL can be achieved through micro-pits prepared by the laser-ablation technique. Well-defined sharp lasing peaks were realized based on the coherence feedback process in the 1D optical waveguide. The near- and far-field images exhibit excellent spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…It is observed that the lasing wavelength of BFRL filled with MCF-7 cells has a 2.3 ± SE 0.2 nm blue shift with respect to that with MDA-MB-231 cells. This lasing wavelength shift phenomenon has been observed in previous studies, wherein the scattering strength of the random laser system is variable. ,, The corresponding mechanism can be illustrated on the basis of the analysis of another important biophysical property, the refractive index. For example, Hu et al shows that the 0.011 refractive index variation could result in a spectral shift of up to 18.5 nm .…”
Section: Resultssupporting
confidence: 60%
“…It is observed that the lasing wavelength of BFRL filled with MCF-7 cells has a 2.3 ± SE 0.2 nm blue shift with respect to that with MDA-MB-231 cells. This lasing wavelength shift phenomenon has been observed in previous studies, wherein the scattering strength of the random laser system is variable. ,, The corresponding mechanism can be illustrated on the basis of the analysis of another important biophysical property, the refractive index. For example, Hu et al shows that the 0.011 refractive index variation could result in a spectral shift of up to 18.5 nm .…”
Section: Resultssupporting
confidence: 60%
“…Reducing the size of a random laser to microscale opens up many potential applications such as on‐chip optical communications, data processing, and biointegration. [ 13 ] To date, random microlasers are highly limited to semiconductor‐based structure such as the clusters of ZnO nanoparticles, [ 14 ] and ZnO microwires [ 15 ] whereas organic random lasers generally have a larger size in a range of millimeter scale. [ 16–18 ] Compared with semiconductor random microlasers, organic random microlasers may have several advantages including low‐cost fabrication, flexible properties, and lightweight.…”
Section: Introductionmentioning
confidence: 99%
“…Although these defect-related micropits were considered destructive for electron transport, , they have a strong scattering feedback effect for light propagation in the MW. Especially, the scattering feedback from the micropits can localize the light field and form localized paths to construct the RL action . A schematic diagram of the localized paths on RL in the MW is illustrated in Figure c.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although an RL has been observed in GaN nanocolumns, particles, and epitaxy films, , the manipulation of the lasing mode and output divergence is a great challenge for two- and three-dimensional disorder media. Recently, the manipulation of the RL mode in a one-dimensional microwire (MW) may open a new horizon of optimization for GaN RLs …”
mentioning
confidence: 99%